The political economy of 'linked' progressive taxation in Africa and Latin America - Paul Mosley; Abdul-Gafaru Abdulai (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
One key element in the reduction of poverty and (in Latin America) inequality has been the achievement of greater fiscal equity; we analyse one key part of this process, which is the earmarking of portions of tax revenue to be spent on progressive public expenditures such as social protection, health, and education. Such 'linkage' yields a political dividend, and may also help to strengthen the tax base, but at the same time constrains the flexibility with which public revenue can be switched between sectors. We examine, principally by regression methods, the impact of 'linked taxation' in five countries - Bolivia, Ecuador, Venezuela, Zambia, and Ghana - and find that it significantly reduces political instability and raises tax revenue in all those countries. 'Linked progressive taxation' has evolved over recent years to become more flexible, in particular through reforms in the sources and types of taxation which are used to finance priority expenditures, and we argue that these adaptations have helped to reduce the inefficiencies associated with linked taxation.
Keywords: H2; H5; O2; 330; taxation; public expenditure; political economy; redistribution; Africa; Latin America